Microbead design for sustained drug release using four natural gums (2013)
Four natural gums, namely albizia, cissus, irvingia and khaya gums have been characterized and evaluated as polymers for the formulation of microbeads for controlled delivery of diclofenac sodium. The natural gums were characterized for their material properties using standard methods. Diclofenac microbeads were prepared by ionotropic gelation using gel blends of the natural gums and sodium alginate at different ratios and zinc chloride solution (10%w/v) as the crosslinking agent. The microbeads were assessed using SEM, swelling characteristics, drug entrapment efficiencies and release properties. Data obtained from in vitro dissolution studies were fitted to various kinetic equations to determine the kinetics and mechanisms of drug release, and the similarity factor, f2, was used to compare the different formulations. The results showed that the natural gum polymers varied considerably in their material properties. Spherical and discrete microbeads with particle size of 1.48–2.41μm were obtained with entrapment efficienciesof 44.0–71.3%w/w. Drug release was found to depend on the type and concentration of polymer gumused with formulations containing gum:alginate ratio of 3:1 showing the highest dissolution times. Con-trolled release of diclofenac was obtained over for 5 h. Drug release from the beads containing the polymer blends of the four gums and sodium alginate fitted the Korsmeyer–Peppas model which appeared to be dependent on the nature of natural gum in the polymer blend while the beads containing alginate alone fitted the Hopfenberg model. Beads containing albizia and cissus had comparable release profiles to thosecontaining khaya (f2> 50). The results suggest that the natural gums could be potentially useful for the ormulation controlled release microbeads.